These men chose hell - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Fort Misery, 2025)
"They're not what you'd call 'the good guys'. They're a mangy pack of despicable deserters, thieves, mutineers, and worse. But as condemned soldiers in an overstretched army, they were given a choice: death by hanging or serving out their time in a hell on earth. These men chose hell. Located at the farthest edge of the Yuma Desert, Fort Grierson is a magnet for trouble. Vicious attacks by marauding Apaches and gunslinging outlaws are practically a daily occurrence -- and the men holding down the fort are hardly any better. Hence the nickname Fort Misery." -- Provided by publisher.